Hemostatic Status of Pre and Post Intracoronary Injection of Peripheral Blood Stem Cells in Patients with Recent Myocardial Infarction - Cosphiadi Irawan; Teguh Santoso; Djumhana Atmakusumah; Idrus Alwi; Agus Kosasih; Auda Aziz; Abdulmuthalib Abdulmuthalib; Lyana Lyana; Sri Inggriani; Ardian Saputra; Merry Wintery; Linda Lison; et al. (Acta Medica Indonesiana, 2016)
Aim: to investigate hemostatic parameter changes, such as platelet aggregation, blood and plasma viscosity, prothrombin time, APTT, CRP and fibrinogen, before and after administration of stem cell therapy. Methods: a total of 24 patients were enrolled. Peripheral blood stem cells (PBSCs) were harvested and injected into the infarct-related artery after 5 consecutive days of G-CSF administration. Recombinant human erythropoietin was administered at the time of intracoronary PBSCs injection. Results: we were able to evaluate 11 from 24 of patients regarding hemostatic status pre–post stem cell injection. There were no significant difference between baseline vs 3 months in spontaneous aggregation (p=0.350), PT (p=0.793), aPTT (p=0.255) and TT (p=0.254). There were also no significant difference between baseline vs 3 months in plasma viscosity (p=0.442) and blood viscosity (p=0.843). Nevertheless the patient who had their blood and plasma viscosity above or below normal laboratory range return to normal level after the treatment. Both PT and APTT also show normalization value. Both Fibrinogen and CRP level show significant decrease between baseline and 3 months after treatment (p=0.009) and (p=0.04) respectively. Conclusion: combined G-CSF and EPO based-intracoronary infusion of PBSCs may open new perspective in the treatment of hypercoagulable state post AMI.